Is it the subcoracoid impingement or the subacromial impingement that tears the subscapularis tendon? A comparison of the MRI findings of the operated and healthy shoulders of the patients - Çetinkaya, Mehmet; Kaptan, Ahmet Yiğit; Ulucaköy, Coşkun; Orhan, Özlem; Topal, Murat; Ayanoğlu, Tacettin; Kanatlı, Ulunay (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2023)
: The purpose of this study is to investigate whether the etiological factors accepted as causes of idiopathic subscapularis tears are true or not when the comparison is made with the opposite side healthy shoulder of the patients who underwent arthroscopic repair for an isolated subscapularis tear.Sixteen patients who underwent shoulder arthroscopy between February 2016 and January 2018 and were diagnosed with isolated subscapularis tear were evaluated. The coracohumeral distance (CHDax), coracoid overlap (CO), and tuberculum minus cysts (TMC) were evaluated on the axial images of the MRI studies while the acromiohumeral distance (AHDsag), CHDsag, and subscapularis tendon slip number (STSN) on the sagittal oblique images and the AHDcor and SLAP lesion on the coronal oblique images. Degeneration of the coracoacromial ligament was evaluated during arthroscopy.The mean CHDsag (11.26-10.08), CHDax (10.63-9.98), CO (14.2-15.43), AHDsag (8-7.66), and AHDcor (7.65-7.68) measurements (operated side-healthy side, respectively) were statistically similar (p > 0.05). No statistically significant difference was found between TMC and STSN in healthy and operated shoulders (p > 0.05). There was mild coracoacromial ligament fraying in 4 (25%) and obvious coracoacromial ligament fraying in 8 (50%) which indicated subacromial impingement in 75% of the patients.The parameters of the coracoid process did not reveal any significant difference between the operated (for an isolated subscapularis tear) and opposite-side healthy shoulders of the patients. However, coracoacromial ligament degeneration was present in 75% of the patients.
Keywords: Shoulder Joint; Subscapularis Tear; Subscapularis Tendon; Magnetic Resonance Imaging; Rotator Cuff Injuries; Upper Extremity; Rotator Cuff; Arthroscopy; Shoulder Impingement Syndrome; Subcoracoid Impingement; Humans; Subacromial Impingement; Research Article